ETMR-01. Management of CNS tumor with BCOR internal tandem duplication with multimodalities therapy: Surgery, Intensive Chemotherapy, and Radiation. (3rd June 2022) - Mobark, Nahla Ali; Alharbi, Musa; Ballourah, Walid; Alsultan, Abdulrahman; El Manjomi, Fahad; AlNaqib, Zaid; Al-Banyan, Ayman; Balbaid, Ali Abdullah O; Abedalthagafi, MD, Malak
Abstract: The 2021WHO CNS tumor classification includes CNS tumors with internal tandem duplications in the BCL6 corepressor (BCOR) gene as a new entity of CNS embryonal tumors labelled high-grade neuroepithelial tumors with BCOR alterations (HGNET-BCOR) are characterized by genetic aberrations in the BCOR gene located at Xp11.4, leading to increased expression of BCOR mRNA and distinct DNA methylation profiles. currently no agreement on the optimal strategy to manage these rare tumors, which mostly occur in young children These tumors are usually treated as high grade glioma HGG with upfront radiation therapy with poor outcome. We report 2.5 years old boy presenting with headache and vomiting. MRI showed a well-defined left cerebellar mass, hyperintense in T2 and hypointense in T1, with restricted diffusion and no spinal CSF seeding metastases. He underwent gross surgical resection of the tumor initial pathological diagnosis was epithelioid high grade malignant neoplasm. Brain tumor methylation classifier analysis of resected tumor tissue confirmed a CNS tumor with BCOR internal tandem duplication (WHO grade 4). The patient was treated per COG ACNS0334 (3 induction cycles of vincristine, cyclophosphamide, cisplatin, etoposide, HDMTX, followed by consolidation with 3 cycles of carboplatin and thiotepa with autologous hematopoietic stem cell rescue). MRI brain before the start of chemotherapy showed a small recurrent mass within the surgical cavity. post-induction MRI detected stable-sized residual lesion in the surgical cavity; however, post-consolidation MRI showed complete resolution of the residual mass. The patient subsequently received craniospinal irradiation (36 Gy [CSI]) with a boost to the tumor bed up to 54 GY. By the time of writing this report our patient is still in complete remission. Our case showed that this aggressive brain tumor may respond well to intensive multimodalities therapy Further case studies and international prospective trials are needed to optimize the clinical management of these rare tumors.